Roles performed by clinical teachers in undergraduate medical education of Bangladesh (Bangladesh Journal of Medical Education, 2017)
A clinical teacher has dual roles to perform in undergraduate medical education along with a major role as patient management. But these roles are not clearly recognized by them. That's why views of clinical teachers and students about roles performed by clinical teachers in undergraduate medical education were studied in eight different government and private medical colleges within and outside Dhaka city. Two sets of questionnaires were developed for teachers and students to explore their views on roles performed by teachers. Total 671 clinical students and 88 clinical teachers having at least two years teaching experience were included. Convenient sampling techniques were used. Seven major roles of clinical teachers were taken into consideration against which teachers and students were expressed their views. Roles were 1. Information provider in the class 2. Role model for the students 3. Students facilitator 4. Curriculum executor. 5. Instructional material creator 6.Student's assessor and 7. Role of teachers on research activities. In this study 52.27% teachers had experience on workshop and training on teaching methodology and 38.82 % had no experience on teaching and learning. Teachers expressed their views against their performances of all the roles for more than two third classes. While students viewed against teachers performances in less than a half of the classes. Teachers mentioned that excess clinical load, administrative work and bad political environment hampered their teaching roles. They also suggested that different courses on teaching and learning, teacher's evaluation system and regular faculty development programme would help to improve in clinical teaching.Bangladesh Journal of Medical Education Vol.6(1) 2015: 19-23